Erarbeitung einer Methodik zur Abbildung tribologischer Bedingungen im Presshärteprozess unter Verwendung einer Warmstreifenziehanlage mit Umlenkung - He, Franz; Harms, Arnold; Merklein, Marion (Tagungsband zum 19. Erlanger Workshop Warmblechumformung 2024, 2024)
Im Automobilbereich hat sich das Presshärten als Herstellungsverfahren für sicherheitskritische Komponenten in der Karosserie wie der B-Säule etabliert. Durch die Austenitisierung des Bor-Mangan-Stahls bei Temperaturen über Ac3 kann die Maßhaltigkeit gesteigert und die Rückfederung gesteigert werden, wenn bei hohen Temperaturen umgeformt wird. Der Kontakt mit dem gekühlten Werkzeug löst zusätzlich eine Martensithärtung aus, wodurch das finale Bauteil bei Raumtemperaturen gute mechanischen Eigenschaften und insbesondere hohe Festigkeiten aufweist. Aufgrund der hohen Temperaturen ist ein Einsatz von Schmierstoffen bisher nicht möglich. Um die auftretenden tribologischen Eigenschaften zu untersuchen werden bisher Laborversuche über eine flache Ebene genutzt, die die Kontaktbedingungen im Flanschbereich wiedergeben. Da sich der kritische Bereich der Ausdünnung und Verschleißentstehung im Bauteil auf die Kontaktzone im Matrizeneinlaufradius konzentriert, wurde mit dem Streifenzug mit Umlenkung ein neuer Versuchsprüfstand adaptiert, um die Verhältnisse in der Wirkfuge am Werkzeugradius wiedergeben zu können.<br
Keywords: Presshärten; Tribologie; Umlenkung; 22MnB5; Aluminium-Silizium

Non-destructive testing in versatile joining processes - Lechner, Michael; Borgert, Thomas; Busch, Matthias; Harms, Arnold; Holtkamp, Pia; Kappe, Fabian; Römisch, David; Wituschek, Simon (Sheet Metal 2025, 2025)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT’s application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysi
Keywords: Computed Tomography; Metrology; Mechanical Joining

Numerical and experimental investigation on the material flow in an orbital forming process to join functional components from dissimilar materials - Harms, Arnold; Hetzel, Andreas; Lechner, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2025)
The manufacturing industry is currently facing major challenges. Environmental protection requirements, component complexity and material costs are continually growing. Lightweight design offers a solution, particularly in hybrid components, reducing weight while maintaining strength. Joining by forming processes based on plastic deformation offer high material efficiency and a reduced number of required parts. However, industrially established processes oppose a lack in flexibility for varying material thickness and strength class. Current research focuses on innovative and versatile mechanical joining processes. In this context, the process of orbital forming was investigated to be used as mechanical joining operation for dissimilar materials. The rotational movement of the tool enables a radial material flow, ensuring permanent form and force closure. To establish a reliable joint, a fundamental understanding of the process in terms of the material behavior is necessary. Therefore, the main focus of this investigation is introducing a novel numerical and experimental approach to identify the material flow during forming. A numerical model is utilized to simulate an orbital forming process and analyze the stress conditions as well as the resulting material flow. The joining partners include the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 3.0 mm. The numerical simulation indicates that with increasing forming force, the material flow increases due to elevated compressive stresses. This assumption is confirmed by experimental investigations using various forces. In addition, the geometrical and mechanical properties of the joint were measured in further investigations, in order to validate the numerical process model.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Forming; hybrid semi-finished components; lightweight design; mechanical joining; numerical modeling; orbital forming; sheet-bulk metal forming; simufact forming; versatile joining process